Manajemen Kompetensi Guru Dalam Meningkatkan Daya Saing Lembaga Pendidikan Anak Usia Dini Di Era Pandemi COVID-19 - Rifka Toyba Humaida; Erni Munastiwi (STAI Publisistik Thawalib Jakarta, 2022)
Competitive Early Childhood Education Management is a systemic and systematic activity carried out by the head to improve the performance of educators through various Early Childhood Education activity programs that are in accordance with the standards and development of children. The approach used in this research is a qualitative approach using the case study method. The data collection techniques used are observation, interviews, and documentation studies. The results of this study are that the planning carried out by the principal and educators of Thoyyibah Kindergarten is divided into three stages, namely long-term, medium-term and short-term planning, the implementation follows include teachers in education and training programs, while development is to provide supporting facilities. The conclusion of this study is that teacher education and training is an alternative in increasing competence, it is recommended that the problem is that teachers lack competence. The solution is teacher education and training.